SARS-CoV-2 Nsp5 Activates NF-κB Pathway by Upregulating SUMOylation of MAVS - Li, Weiling; Qiao, Jialu; You, Qiang; Zong, Shan; Peng, Qian; Liu, Yuchen; Hu, Song; Liu, Wei; Li, Shufen; Shu, Xiji; Sun, Binlian (Frontiers in Immunology, 2021)
The COVID-19 is an infectious disease caused by SARS-CoV-2 infection. A large number of clinical studies have found that high-level expression of pro-inflammatory cytokines in patients infected with SARS-CoV-2，which is one of the important reasons for the rapid development of the disease, but the specific molecular mechanism is still unclear. This study found that SARS-CoV-2 Nsp5 can induce the expression of cytokines IL-1β, IL-6, TNF-α and IL-2 in Calu-3 and THP1 cells. Further research found Nsp5 enhances cytokines expression through activating NF-κB signaling pathway. Next, we investigated the upstream effectors of the NF-κB signal pathway upon Nsp5 overexpression and discovered that Nsp5 increased the protein level of MAVS. Moreover, Nsp5 can promote the SUMOylation of MAVS to increase its stability and leading to the increasing of MAVS protein, at last triggering activation of NF-κB signaling. And knockdown of MAVS and the inhibitor of SUMOylation treatment can attenuate Nsp5-mediated NF-κB activation and cytokine induction. Taken together, this study identified a novel role of SARS-CoV-2 Nsp5 to enhance cytokine production by activating NF-κB signaling pathway.